2017
DOI: 10.4236/ajor.2017.72010
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Listed Companies in the UAE-Using DEA Malmquist Index Approach

Abstract: Data Envelopment Analysis (DEA) is becoming an increasingly popular tool for assessing the relative performance of industries and companies. By applying DEA theory to the non-financial sector, the relative efficiency of 27 listed corporations in the United Arab Emirates (UAE) has been analyzed in this paper. The focus of the study has been on the impact of the financial crisis and the recovery thereafter. Further, the productivity change was decomposed into technical efficiency change and technological change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In the work of (Zhiyong et al, 2017) the cross-sectional DEA models were extended to time -varying malmquist DEA, results based on a sample of 742 Chinese listed companies observed over 10 years suggested that malmquist DEA offers insights into the competitive position of a company in addition to accurate financial distress predictions based on the DEA efficiency measures. (Majumdar and Asgari, 2017) applied DEA theory to analyze the relative efficiency of 27 listed corporations in the United Arab Emirates, and studied the impact of the financial crisis and the recovery thereafter. They used malmquist productivity Index to study the decomposition of the productivity change for the period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of (Zhiyong et al, 2017) the cross-sectional DEA models were extended to time -varying malmquist DEA, results based on a sample of 742 Chinese listed companies observed over 10 years suggested that malmquist DEA offers insights into the competitive position of a company in addition to accurate financial distress predictions based on the DEA efficiency measures. (Majumdar and Asgari, 2017) applied DEA theory to analyze the relative efficiency of 27 listed corporations in the United Arab Emirates, and studied the impact of the financial crisis and the recovery thereafter. They used malmquist productivity Index to study the decomposition of the productivity change for the period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stochastic frontier analysis (SFA) and data envelopment analysis (DEA) are the most employed parametric and non-parametric methods in the literature respectively (Silva et al, 2017). DEA is an optimization method that uses linear programming for assessing the efficiency and productivity of decision making units (DMUs) in term of proportional change in inputs or outputs (Majumdar and Asgari, 2017). Data envelopment analysis method was first introduced by (Charnes et al, 1978), and for this reason it is known as the CCR model, the CCR model assumes constant return of scale production function, then (Banker et al, 1984) modified this model and assumes the variable return to scale (VRS) efficiency measurement model, which is also known as the BCC model according to the names of the authors.…”
Section: Introductionmentioning
confidence: 99%
“…In Van der Westhuizen (2008) the efficiency and causes for efficiency change were evaluated for the four largest banks in South Africa for a period of 36 months. Majumdar and Asgari (2017) studied the performance measurement of UAE companies by DEA Malmquist. They used labor, capital, materials, revenue and EPS as the inputs and outputs of the model.…”
Section: Banking Industrymentioning
confidence: 99%
“…Different measures have been used as a proxy for the capital input, namely: Total fixed physical capital in money term (Lee and Tyler, 1978), value of tangible fixed assets other than land (Tsukamoto, 2019), the replacement value of Capital (Suyanto et al, 2014), the net book value of the property, plant, equipment under the non-current assets of the Balance Sheet (Majumdar and Asgari, 2017), the replacement cost of existing machinery and other equipment employed in the production process, corrected by the degree of capacity utilization (Lundvall and Battese, 2000) the net value of fixed assets at the end of the survey year (Hailu and Tanaka, 2015), total assets (Dietrich, 2010) and (Le et al, 2018). The noncurrent asset is used in this study for the capital input.…”
Section: Capital (Input Variable)mentioning
confidence: 99%